Rate Coefficients Adjustments and Diagnostics Methods for \(N\) and \(H\) Atom Densities in \(R(Ar, He)-N_2-H_2\) Afterglows: Insights from TALIF and OES Measurements - Ricard, A.; Amorim, J.; Sarrette, J. P. (Plasmas Afterglows with N\(_2\) for Surface Treatments New Results, 2024)
It is deduced from recent results obtained in the Laplace Lab. concerning the TwoPhoton Laser Induced Fluorescence measurements (TALIF) of \(N\) and \(H\) atoms densities in \(N_2-H_2\) afterglows that the rate coefficient of the \(N+H+M\left(N_2, Ar\right) →\) \(NH+M\left(N_2, Ar\right)\) reaction chosen in Chapters 2,4 and 13 of the previous books (A. Ricard - Plasmas afterglows with \(N_2\) for surface treatments, editions 1-3, Bookpi 2021-23) must be divided by 50 for \(M=N_2\) and by 20 for \(M=A r\). This result confirms the assumed rate coefficient value of \(10^{-33} ~cm^6 ~s^{-1}\) for \(M=N_2\) given by Gordiets (B. Gordiets, C.M. Ferreira, M.J. Pinheiro and A. Ricard, Plasma Sources Sci. Technol. 7 (1998) 363). The concerned chapters of the previous BPI book have been corrected with these new data. It also discussed two methods to obtain the \(a_{N+N}\) fraction of the \(N+N\) recombination producing the \(N_2(B, 11)\) radiative state, conducting in a variation by a factor comprised between 1 and 1.4 on the previous \(N\) and \(H\) atoms densities. It has been chosen a rate coefficient for the \(N+H+M\left(N_2, A r\right) → NH+M\left(N_2, A r\right)\) reaction of (1-3) \(10^{-33} ~cm^6 ~S^{-1}\) for \(M=N_2, Ar\). The \(y\)-destruction probability on the quartz tube wall was found to be \(50^{-3}\), about 10 times higher than for \(N\)-atoms. It was deduced a dissociation of about \(50 % H_2\) in \(N_2 / 0.1 % H_2\) and \(100 %\) in \(Ar / 2 % ~N_2 / 0.1 % H_2\) early afterglows (time \(10^{-3} ~s\) ) for gas pressure in the 4-8 Torr range.